2002
DOI: 10.1046/j.0269-283x.2002.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

L‐lactic acid: a human‐signifying host cue for the anthropophilic mosquito Anopheles gambiae

Abstract: Abstract. Using a dual-choice olfactometer, the role of L-lactic acid was investigated in relation to host-seeking and selection by female Anopheles gambiae Giles sensu stricto (Diptera: Culicidae) mosquitoes in a Y-tube bioassay. L-lactic acid alone was not attractive, but it significantly augmented the attractiveness of CO 2 , skin odour and skin-rubbing extracts from humans and other vertebrates. Comparing the left and right index fingers of the same person, one could be made more attractive than the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 33 publications
5
129
1
2
Order By: Relevance
“…The low sensitivity of the lactic acid-detecting ORNs and the low vapor phase of lactic acid required large amounts of stimulus (10 g) thus defeating the purpose of comparing neuronal activity in the presence and absence of DEET. We also tested the yellow fever mosquito, Aedes aegypti, but preliminary recordings (data not shown) showed a similar low sensitivity of the peg sensilla to lactic acid, in line with both the high titer of lactic acid in human sweat (8) and the doses required for mosquito attraction (9). Given the technical difficulty of reexamining DEET effect on lactic acid detection and considering DEET repellency to mosquitoes attracted only to carbon dioxide (4, 7) we then examined the possible effect of DEET on CO 2 detection.…”
Section: Resultsmentioning
confidence: 99%
“…The low sensitivity of the lactic acid-detecting ORNs and the low vapor phase of lactic acid required large amounts of stimulus (10 g) thus defeating the purpose of comparing neuronal activity in the presence and absence of DEET. We also tested the yellow fever mosquito, Aedes aegypti, but preliminary recordings (data not shown) showed a similar low sensitivity of the peg sensilla to lactic acid, in line with both the high titer of lactic acid in human sweat (8) and the doses required for mosquito attraction (9). Given the technical difficulty of reexamining DEET effect on lactic acid detection and considering DEET repellency to mosquitoes attracted only to carbon dioxide (4, 7) we then examined the possible effect of DEET on CO 2 detection.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, S1 sensillum neurons showed no response to isovaleric acid, which evokes strong ELG responses ( Fig. 1) as well as 1-octen-3-ol, 2-methyl phenol, 4-methyl phenol, indole, geranyl acetone, and ammonia, which have been identified as human sweat compounds and shown to elicit significant responses from A. gambiae antennal preparations (14,15,(19)(20)(21), (Fig. 1D).…”
Section: Characterization Of Olfactory Responses From the Proboscis Omentioning
confidence: 99%
“…Female Anopheles gambiae, the main malarial vector in Sub-Saharan Africa, rely on their sense of smell for host seeking, oviposition and sugar feeding, whereas males respond mostly to plant odors (Foster, 1995;Takken and Knols, 1999). Many field and laboratory studies have shown that female A. gambiae respond to odors emitted from humans to find a blood meal, and wind tunnel experiments and electroantennograms (EAG) have identified a variety of singlechemical compounds in human sweat that stimulate olfactory neurons and attract female mosquitoes (Cork and Park, 1996;Costantini et al, 2001;Dekker et al, 2002;Meijerink et al, 2001;Meijerink and van Loon, 1999;Qiu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%